PRACTICAL PROBLEMS IN GOVERNMENTAL ACCOUNTING. - Bailey, George D. (The Accounting Review, 1939)
Abstract One of the important practical problems in governmental accounting is the preparation of reports the essentials of which can be understood by the reasonable informed portion of the public. There are two methods of approach to the problem of increasing the public's understanding of financial reports. One approach is through education, colleges and universities have been doing practically all the educating that has been done. Through the colleges, the courses of business administration have been sending forth each year a substantial number of people who, being fairly conversant with the various problems of municipal accounting, were in a position to understand the financial reports of their various communities if, as, and when presented to them. The second approach to the problem is in the presentation of municipal financial reports. Each report when issued might contain some explanation of the operation of the fund principle upon which the reports are prepared. Care must be exercised in the number of funds displayed in these columnar reports, and often combination of similar funds can properly be made for this columnar presentation. Certainly the report to be effective must make comparisons of the budgets with the actual performance. Each report requires careful study so that such budget comparisons may be informative without being so voluminous as to be confusing.